Assessment of Prospects for the Development of the Life Insurance Market in the Context of Reforming the Pension System - Savytska Nataliia L. (Problemi Ekonomiki, 2019)
The aim of the presented research is to deepen the theoretical bases of and assess the prospects for the further development of the non-state pension sector in Ukraine, namely, life insurance companies as one of the participants in the pension system of the country. The level of development of non-state pension provision in Ukraine is analyzed. There calculated the life insurance coverage, taking into account the population aged 18 to 60, and the number of participants in non-state pension funds of Ukraine. A comparative analysis of financial services for the provision of supplementary pensions rendered by non-state pension funds, banking institutions, and life insurance companies is carried out. Based on the analysis, the competitive advantages of life insurers over other financial institutions that provide accumulative pension insurance services are formulated, which made it possible to identify prospects for the development of life insurance services in the context of reforming the pension system in Ukraine. As a result of the study, there set the tasks the implementation of which will allow life insurers using development opportunities and taking a leading position in the market for the provision of non-state pension insurance services.